(untitled) (African Journal of Biomedical Research, 2024)
This study assessed the effect of supportive education on the knowledge and practice of kangaroo-mother-care (KMC) in the management of pre-mature and low-birth-weight babies in selected communities in Enugu State. A quasi-experimental pretest-posttest, non-randomized design was adopted. A sample size of 332 postnatal mothers from the two community health centers under study was determined using power analysis. A structured questionnaire was used as an instrument for data collection. Data were descriptively analyzed with SPSS version 22, while inferential statistical analysis was performed using the chi-square test, independent t test, and one-way analysis of variance. Results with a p < 0.05 were considered statistically significant. Results of major findings showed that mothers' knowledge of KMC improved after the intervention, from an average score of 34.8% to 85.6% and 31.9% to 69.2%, with mean and standard deviations of 6.8±2.6 and 5.6±2.9 in the experimental and control groups, respectively. The practice of KMC also improved after the intervention, from 30% to 76.6% and 36.4% to 73.5%, with mean and standard deviations of 7.7±1.2 and 6.6±1.5 in the experimental and control groups, respectively. There was a significant difference in mothers knowledge of KMC between the experimental and control groups before the intervention (t =2.6 and p = 0.010) and after the supportive intervention (t = 3.7 and p = 0.000). There was no significant difference in the influence of socio-demographic characteristics of mothers and the practice of KMC after intervention in both groups: educational status (F = 0.3 and p = 0.801), marital age (F = 0.3 and p = 0.889), and parity (F = 0.1 and p = 0.965). In conclusion, participants with supportive education interventions (experimental group) performed better than those with normal health education (control group).